Efficacy of autologous platelet rich plasma versus regular dressing in chronic wounds - ., Asif; Chandramouli, N. (International Surgery Journal, 2019)
Background: Chronic wounds are a frequent problem and pose a heavy burden to the service provider. Platelet extract containing several growth factors used on chronic wounds has shown impressive results in both healing percentage and time for epithelisation. Platelet extract from the patient’s own blood has been used in trials as a cheap and equally effective alternative to commercial platelet gels. The aim of the study was to demonstrate the therapeutic role of autologous platelet rich plasma (APRP) in epithelialisation and reduction in size of chronic wounds of lower limb. Methods: It is a case control study, conducted at Sri Adichunchanagiri Hospital and Research Centre, B.G. Nagara, Karnataka. Conducted during January 2017 to June 2018 this study consisted of 30 patients with chronic ulcers between the age group of 18-80 years, with duration of ulcer ranging from 12 to 26 weeks. After obtaining consent they were randomly allotted into control and test groups with 15 patients each. Control group patients were treated with conventional dressing and in test group APRP dressing was done. Later percentage decrease in wound size was assessed. Results: Ulcer size decreased significantly (p<0.0001) in test group compared to control group. No unwanted effects or complications noted. Conclusions: APRP is a safe and effective treatment modality for chronic non-healing ulcers. It enhances healing and also decreases the associated cost and morbidity. Further research and randomized controlled clinical trials on larger patient population are necessary to validate the results.